THE GLOBAL IT SERVICES MARKET: TRENDS, STRUCTURE AND STRATEGIC RECOMMENDATIONS FOR UZBEKISTAN’S INTEGRATION INTO GLOBAL VALUE CHAINS (2025–2030) - Boburjon Urishov; Zakirova Sayora (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The Market of global IT services is undergoing a structural change, driven by remote computing, implementation of the international digital channels, and the faster offshoring of digital labor. The present article explores trends of the industry globally, relative competitiveness, and reconfiguration of the industry value chains in the years 2020-2024 with further projection up to 2030. Based on online data from Gartner, IDC, Statista, the World Bank, the author has identified the major vectors of industry growth and assessed the positions of rising economies within the international IT delivery landscape. Special attention is given to the digitally focused economy development strategy in Uzbekistan, and the existing performance of the domestic IT industry, as well as practical policy advice for unlocking the country‘s potential to serve as a global IT services offshoring hub by 2030.